Identifying critical transmission lines in cascading outages using the natural connectivity index - Francisco Rivas-Dávalos; Jorge Sánchez-Jaime; Pedro Acosta-Reyes; Leonel Alvarez-Farias (Discover Electronics)
Abstract This paper presents a novel method for identifying critical transmission lines (CTLs) in power systems subjected to cascading overload outages, leveraging the Natural Connectivity (NC) index. Unlike previous studies that employed suboptimal weights for the edges, this work introduces a new weighting strategy that enhances the effectiveness of NC in CTLs identification. The proposed Weighted Natural Connectivity-based (WNC-based) method is validated through comparisons with established methods, including the catastrophic expectation index, and the cascading failure simulation index, using IEEE test systems of 30, 39, 57, and 118 buses and the 400 kV Mexican power system. The experimental results demonstrate that the WNC-based method accurately identifies critical lines, providing a practical balance between simplicity and precision. This study challenges prior conclusions that natural connectivity is unsuitable for CTLs identification, showcasing its potential in power system applications. Furthermore, the method's applicability extends to interconnected systems, such as the integration of power transmission, gas distribution, and telecommunication networks, paving the way for future research. The WNC-based method offers a practical tool for preventing blackouts and enhancing power grid resilience, contributing significantly to the field of power system reliability and stability.